Pemahaman Orang Tua Di Paud Az-Zahra Dalam Menstimulasi Perkembangan Anak Melalui Pendekatan Steam - Nurakhmaliyah, Siti; Usman, Nurodin (Prosiding University Research Colloquium, 2021)
his research is motivated by the lack of the ability of parents tostimulate children's development at home. Covid 19, which has hitalmost all countries, demands changes in various aspects of life,including education. The Covid 19 pandemic also requires parentsto act as teachers at home. However, in practice, not all parentsare optimal in carrying out their roles, therefore researchers areinterested in conducting research on parental understanding instimulating children's development through the STEAM approach.The research subjects were parents at the Az-zahra EarlyChildhood Education Institute Yogyakarta. The purpose of thisstudy was to determine the extent to which parental understandingin stimulating children's development while learning from home interms of the STEAM approach. The subjects of this study were 20parents of children aged 4-7 years. Characteristics of researchsubjects were parents who had attended training on virutialSTEAM-filled learning. This study uses qualitative researchmethods, which focus on understanding, implementing andevaluating parental activities in stimulating early childhooddevelopment. Data obtained from questionnaires, virtualinterviews, and documents. The results of this study obtained datathat in the principle component of STEAM implementation whichconsists of 6 variables an average percentage of 75% is obtained,while in the STEAM implementation formula component, thepercentage is 83.5%, indicating that parents can understand theSTEAM approach and apply it in stimulating children'sdevelopment while learning from home through materials and toolsaround the home environment.